Computer assisted method for proving existence of periodic orbits - Pilarczyk, Paweł (Topological Methods in Nonlinear Analysis, 1999)
We introduce a method based on the Conley index theory for proving the existence of a periodic trajectory in a smooth dynamical system in R^n where an attracting periodic orbit is numerically observed. We apply this method to prove the existence of a periodic orbit in the Rössler equations, as announced in [< i> Computer assisted proof of the existence of a periodic orbit in the Rössler equations< /i> ].